Night animals - Komunyakaa, Yusef (Quarternote chapbook series, 2020)
"The poems in Night Animals, by Yusef Komunyakaa, climb so deeply into the being of various beasts, from cricket to leopard to snowy owl, that we read them with an uncanny shiver of recognition. Without ever fully abandoning his human skin, Komunyakaa inhabits both the outer and inner lives of these creatures. The images are a brilliant match for the poems, each of Rachel Bliss's surreal animals populate a realm somewhere between our two species-birds with teeth, men with antlers, a duck wearing suspenders. Both image and word are dense and dark, intensely focused around a kind of hunger. The poet has been startling us with his rich, disturbing, and important poems for many years. Night Animals extends Yusef Komunyakaa's remarkable oeuvre"--